Fracture Characteristics and its Role in Bedrock Reservoirs in the Kunbei Fault Terrace Belt of Qaidam Basin, China - Wang, Zhaosheng; Xiang, Hui; Wang, Libin; Xie, Lin; Zhang, Zhenguo; Gao, Lianfeng; Yan, Zhifeng; Li, Fuling (Frontiers in Earth Science, 2022)
Fracture development at bedrock reservoirs in the Kunbei fault terrace belt in the southwest of Qaidam Basin, China, is investigated based on cores, thin sections, microresistivity scanning imaging log and production test. Results show that the weathered unitat the top of bedrocksis not effective reservoir because of extremely-low porosity. Semi-weathered unit is potential reservoir, where formation water migrating along early effective fractures could develop dissolution fractures and pores as primary storage space, and fractures can also act as seepage channels. Four fracture types can be identified from bedrock reservoirs, .e.g., structural ones, diagenetic ones, weathering ones and dissolution ones, while shear fractures related to faults are the most important ones. Fracture types and development vary greatly between granite and slate, while high fracture density resulted in intensive dissolution in granite. The fractures density is closely related to tectonic stress. The bedrock reservoirs near fault zones and semi-weathered unit are potential oil and gas exploration targets in the Kunbei fault terrace belt. Effective fractures govern formation and distribution of dissolution fractures and pores as well as dominant seepage direction, which is the key to the accumulation and development of bedrock reservoirs.